Optimisation and evaluation of antibacterial topical preparation from Malaysian kelulut honey using guar gum as polymeric agent - Mohd Amir Shahlan, Mohd Aspar; Raihana Z., Edros; Norul Amilin, Hamzah (Universiti Putra Malaysia Press, 2021)
The study aims to formulate and optimise topical antibacterial preparation using Malaysian kelulut honey as the active ingredient and guar gum as the polymeric agent. Response surface methodology (RSM) was used to optimise the preparation. The acidity, honey concentration, and guar gum concentration were the independent variables. Meanwhile, the zone of inhibitions on Staphylococcus aureus ATCC6538 and Escherichia coli ATCC8739 were the response variables. The optimal preparation was evaluated on its physicochemical properties, viscosity, antibacterial efficacy, and stability. The antibacterial efficacy of the optimal preparation was compared to the commercial antibacterial gel (MediHoney™, Comvita). The optimal preparation was formulated at pH 3.5, honey concentration of 90% (w/v), and guar gum concentration of 1.5% (w/v). The inhibition zones measured on S. aureus ATCC6538 was 16.2 mm and E. coli ATCC8739 was 15.8 mm, respectively. The optimal preparation showed good physicochemical properties and effective antibacterial properties. However, the viscosity of the preparation was reduced by more than 50% during the six months of the stability study. Guar gum is a potential polymeric agent in preparing kelulut as topical preparation with effective antibacterial properties. Consideration of additional stabilising or preservative agent is recommended to overcome the reduction of viscosity over time.